Traditional Game â€œBakiakâ€ Assisted Project-Based Learning Model Influences Studentsâ€™ Social Skills - A.A.Sg Paramita Ari Putri; I Wayan Sujana (Jurnal Ilmiah Sekolah Dasar, 2020)
The problems that underlined this research included: the development of children's social skills was still not optimal, learning models in the classroom were less varied, including in the selection of media and, the interaction of students with other students was still lacking so that learning was still monotonous and less interesting. This study aimed to analyze the effect of the project-based learning model which is assisted with traditional clogs toward the social skills of the fifth-grade elementary school students. The study applied a non-equivalent control group design. Determination of the sample applied random sampling techniques. The population of this study was all students of class V. In this study, the obtained samples were 62 people. Data collection applied observation techniques. The instrument was the observation sheet. The calculation results of average gain in studentsâ€™ social skills scores were given the treatment of project-based learning models in which learning was assisted with traditional game clogs included 0.295 in the category of very sufficient, while students who were taught conventional learning models had an average score of social skills score of -0.022 , belongs to the less category. Thus, based on these findings, it can be concluded that the project-based learning model assisted by traditional game clogs influences the social skills of fifth grade elementary school students. This model can be used as a choice by teachers to be used as an alternative to improve social skills.